A primer about storage in bottom-up models of future energy systems. Fundamentals of storage operation and investment in competitive long-term equilibria - Benjamin Böcker; Christoph Weber (University of Duisburg-Essen, House of Energy Markets & Finance (HEMF), 2020)
Growing shares of renewable energy sources (RES) in the electricity system increase the need for flexible balancing of supply-dependent feed-in of RES and time-varying demand. Besides flexible, conventional technologies and demand-responses, storage is an important option. Through the use of an analytical approach, this paper explores the implications of the short- and long-run electricity market equilibrium. While conventional and renewable technologies have fixed positions in the supply stack depending on their operational costs, storage may shift in the supply stack over time. Hence, shifts in the supply stack only occur if the storage is either full or empty; otherwise, the so-called shadow price of storage is constant. In a long-term partial electricity market equilibrium, this implies more complicated patterns of operational cash flows for storage technologies. These cash flow patterns will determine, in turn: how storage investments pay off, to what extent storage is part of an efficient energy system, and what power-to-energy ratio should storage have. The implications for future sustainable energy systems with multiple storage technologies are illustrated in a stylized application of Lithium-Ion batteries and pump hydro storage as two possible storage technologies.
Keywords: Q41; Q43; D41; C68; 330; energy storage; electricity market equilibrium; analytical approach; power system dynamics